Moderating Effect of Information Sharing On the Relationship of Supply Chain Management Capabilities and Business Performance: A Study of the Food Industry - Sittichai Pintuma; Martusorn Khaengkhan; Phutthiwat Waiyawuththanapoom; Wissawa Aunyawong (International Journal of Supply Chain Management, 2020)
Indonesia is viewed as one of the biggest exporters and producer of foods and also plays an essential role in the development of Indonesia economy. Nevertheless, food industry provides help to the country to generate high level of income. To effect the performance of food industry, there are lot of factors. For this purpose, it is intensively challenging to choose that factor which effects more in the performance of food industry that could lead to a negative or the positive impact on another factor. Therefore, objective of the study is to explore the moderating effect of the information sharing on the relationship of supply chain management (SCM) capabilities and business performance (BP) of Indonesia food industry. Using cross sectional research design, 500 questionnaires were distributed among the supply chain managers of food industry by using a judgmental sampling technique which yield a 40% response rate. The data was analyzed by the Structural Equation Modeling technique. The key findings of the study have shown that SCM capabilities have positive and significant association with the BP. Similarly, it was also shown that information sharing significantly moderates within two components of SCM namely, strategic sourcing, technology capability and BP. Whereas has insignificant moderating effect on the relationship of logistic integration commitment and BP.  Hence, current study contributed some theoretical implications in the existing body of literature. The study limitations and future directions are also being discussed.